DNA Barcoding of Nematodes Using the MinION - Knot, Ineke E.; Zouganelis, George D.; Weedall, Gareth D.; Wich, Serge A.; Rae, Robbie (Frontiers in Ecology and Evolution, 2020)
Many nematode species are parasitic and threaten the health of plants and animals, including humans, on a global scale. Advances in DNA sequencing techniques have allowed for the rapid and accurate identification of many organisms including nematodes. However, the steps taken from sample collection in the field to molecular analysis and identification can take many days and depend on access to both immovable equipment and a specialized laboratory. Here, we present a protocol to genetically identify nematodes using 18S SSU rRNA sequencing using the MinION, a portable third generation sequencer, and proof that it is possible to perform all the molecular preparations on a fully portable molecular biology lab - the Bentolab. We show that both parasitic and free-living nematode species (Anisakis simplex, Panagrellus redivivus, Turbatrix aceti and Caenorhabditis elegans) can be identified with a 96-100% accuracy compared to Sanger sequencing, requiring only 10-15 minutes of sequencing. This protocol is an essential first step towards genetically identifying nematodes in the field from complex natural environments (such as faeces, soil or marine sediments). This increased accessibility could in turn improve global information of nematode presence and distribution, aiding near-real-time global biomonitoring.